Study of Intraocular Permeability Enhancement of Brimonidine Tartrate by Formulation in Its In Situ Thermoreversible Gel - Mhetre, Ashwini S. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The present work describes the formulation and evaluation of thermoreversible in situ gel of brimonidine tartrate (BRT) by incorporating penetration enhancers such as Surfactant (Tween 20), Chelating agent (Disodium EDTA), Bile salt (Sodium tourocholate) in various percentage strength in combination with viscosifying agent to improve ocular bioavailability of drug, which will also improve corneal contact time and corneal permeation of drug. Materials and Methods: Thermoreversible ophthalmic gel were prepared by using Cold method by mixing Poloxamer 407 as a thermosensitive polymer, HPMC K4M as viscosifying agent, antiglaucomic drug BRT, Benzalkonium chloride as preservatives and one of the three penetration enhancers use alternatively. A 22 factorial design employed for optimization of BRT gels with HPMC K4M (% X1) and penetration enhancer (% X2) as the prime selected independent variable, which were varied at 2 different levels (low and high). Result and Discussion: Raising concentration of penetration enhancers at the certain limit increase in vitro permeation through goat cornea. At 0.5% w/v concentration of penetration enhancers increase percent drug content, improve apparent permeability coefficient of formulation, and gelation temperature, significantly (P < 0.05). The result revealed that optimized formulation containing Tween 20 as penetration enhancers show dominant increase in permeation of drug. Conclusion: The study reflects that the permeation of BRT influenced by various penetration enhancers concentration and also viscosifying agent, permeation was found to be concentration dependent.